Magic Castle Readers : Apes Find Shapes - A Book About Recognizing Shapes - Moncure, Jane Belk; Friedman, Joy (Elgin, IL : Child's World, 1988)
Four funny apes help Tracy find shapes in the objects around her, including the circle in a doughnut, the triangle in a kite, and the rectangle in a door.
Accelerated Reader AR
Keywords: Recognizing shapes; Early readers